Scene construction deficits in adolescent PTSD are in sensory, rather than spatial, imagery - Marlatte, Hannah; Ryan, Jennifer D.; Gilboa, Asaf (Frontiers in Psychology, 2025)
IntroductionPost-traumatic stress disorder (PTSD) is characterized by memory and imagery disturbances, ascribed in part to structural and functional hippocampal abnormalities. These include impaired mental simulation of past and future events, as well as deficits in imagining novel, neutral, spatially coherent scenes (“scene construction”). Structural hippocampal differences are less consistently found in adolescent PTSD; however, deficits in recalling specific autobiographical memories have been noted.MethodsWe examined scene construction ability in adolescents with PTSD, a presumably hippocampal-dependent process. Forty adolescents were recruited through the community: 26 with diverse trauma exposure (7 with PTSD, 19 without PTSD), and 14 non-trauma-exposed healthy controls. Scene construction performance was compared across groups using non-parametric ANOVAs and was related to PTSD symptom severity regardless of group membership using linear regressions.ResultsNo differences in global scene construction performance were found; however, adolescents with PTSD imagined a smaller proportion of sensory details than control groups. Cognitive ability predicted several aspects of scene construction performance, rather than PTSD severity, as had been expected based on the adult literature. Nonetheless, those higher in avoidance symptoms imagined more person-related details, and trauma-exposed participants also reported feeling more present within their imagined scenes compared to healthy non-trauma-exposed controls.DiscussionTogether, these results suggest that hippocampal-dependent deficits in scene construction as seen in adults are not apparent in adolescence, however, changes in sensory imagery are. These findings provide broader insights into PTSD-related cognitive changes during development and inform interventions for this population that focus on sensory experiencing to promote embodiment, even within one’s “mind’s eye”.